2018
DOI: 10.1200/jco.2017.75.9985
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Chemotherapy Followed by Radical Surgery Versus Concomitant Chemotherapy and Radiotherapy in Patients With Stage IB2, IIA, or IIB Squamous Cervical Cancer: A Randomized Controlled Trial

Abstract: Purpose We compared the efficacy and toxicity of neoadjuvant chemotherapy followed by radical surgery versus standard cisplatin-based chemoradiation in patients with locally advanced squamous cervical cancer. Patients and Methods This was a single-center, phase III, randomized controlled trial ( ClinicalTrials.gov identifier: NCT00193739). Eligible patients were between 18 and 65 years old and had stage IB2, IIA, or IIB squamous cervical cancer. They were randomly assigned, after stratification by stage, to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
299
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 366 publications
(320 citation statements)
references
References 21 publications
11
299
0
10
Order By: Relevance
“…In fact, a recent RCT compared neoadjuvant chemotherapy followed by radical surgery versus CCRT for patients with FIGO stage IB2, IIA, or IIB, and the findings obtained showed that CCRT resulted in superior DFS over neoadjuvant chemotherapy followed by radical surgery. 11 However, the utilization rate of postoperative RTwas very low in that RCT (postoperative RT, 13.3%; postoperative CRT, 9.8%), although the majority of patients had FIGO stage IIB disease (57.2%). 11 Some possible reasons for the discrepancy between the results of that RCT and our results may be the difference of the patient and treatment characteristics such as utilization rate of postoperative RT, FIGO stage, and sample size.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…In fact, a recent RCT compared neoadjuvant chemotherapy followed by radical surgery versus CCRT for patients with FIGO stage IB2, IIA, or IIB, and the findings obtained showed that CCRT resulted in superior DFS over neoadjuvant chemotherapy followed by radical surgery. 11 However, the utilization rate of postoperative RTwas very low in that RCT (postoperative RT, 13.3%; postoperative CRT, 9.8%), although the majority of patients had FIGO stage IIB disease (57.2%). 11 Some possible reasons for the discrepancy between the results of that RCT and our results may be the difference of the patient and treatment characteristics such as utilization rate of postoperative RT, FIGO stage, and sample size.…”
Section: Discussionmentioning
confidence: 76%
“…11 However, the utilization rate of postoperative RTwas very low in that RCT (postoperative RT, 13.3%; postoperative CRT, 9.8%), although the majority of patients had FIGO stage IIB disease (57.2%). 11 Some possible reasons for the discrepancy between the results of that RCT and our results may be the difference of the patient and treatment characteristics such as utilization rate of postoperative RT, FIGO stage, and sample size. Therefore, prospective larger studies are needed to examine whether RH with adjuvant RT and definitive CRT are equivalent treatment options for patients with FIGO stage IIB cancer.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…In a prospective, randomized trial, there was no difference in recurrence or death rates for those patients who received NACT versus those who did not before undergoing a radical hysterectomy [31]. Most recently, a prospective, randomized trial of neoadjuvant chemotherapy followed by radical surgery versus standard cisplatin-based chemoradiation for patients with bulky local cervical cancers showed a superior disease free interval for the cisplatin-bases concurrent chemo radiation arm (76.7% versus 69.3% disease-free 5-year survival) [32]. In Bangladesh, 80% women present with advanced stage (Stage III -IV) cervical cancer, and this is fatal in this country [4].…”
Section: Discussionmentioning
confidence: 99%